Economic and Social Factors' Impact on Desa Kebun Kelapa's Financial Performance - Maya Syaula; Geby Citra Ananda; Annisa Ilmi Faried; Indah Safitri Lubis (Yayasan Multidimensi Kreatif, 2023)
This case study examines the influence of economic and social components on village financial performance. At the village level, economic and social factors are two important components that can influence financial welfare and efficiency. In this context, this research focuses on villages in areas inhabited kebun kelapa village. Quantitative analysis is used for both primary and secondary data. Primary data was collected through direct interviews with the head, treasurer and other related staff in the village. Secondary data consists of village financial documents and relevant economic statistics. Multiple linear regression was used to analyze data to determine the influence of economic and social factors on cooperative performance. These results can provide a better understanding of how economic and societal factors influence village financial performance. They can also provide policy recommendations that can help villages with coconut plantations improve their economic performance. In terms of local resource management and rural development, this research is very important.